Visual cortex plasticity evokes excitatory alterations in the hippocampus - Tsanov, Marian; Manahan-Vaughan, Denise (Frontiers in Integrative Neuroscience, 2009)
The integration of episodic sequences in the hippocampus is believed to occur during theta rhythm episodes, when cortico-hippocampal dialog results in reconfiguration of neuronal assemblies. As the visual cortex (VC) is a major source of sensory information to the hippocampus, information processing in the cortex may affect hippocampal network oscillations, facilitating the induction of synaptic modifications. We investigated to what degree the field activity in the primary VC, elicited by sensory or electrical stimulation, correlates with hippocampal oscillatory and synaptic responsiveness, in freely behaving adult rats. We found that the spectral power of theta rhythm (4-10Hz) in the dentate gyrus (DG), increases in parallel with high-frequency oscillations in layer 2/3 of the VC and that this correlation depends on the degree of exploratory activity. When we mimic robust thalamocortical activity by theta-burst application to dorsal lateral geniculate nucleus, a hippocampal theta increase occurs, followed by a persistent potentiation of the DG granule field population spike. Furthermore, the potentiation of DG neuronal excitability tightly correlates with the concurrently occurring VC plasticity. The concurrent enhancement of VC and DG activity is also combined with a highly negative synchronization between hippocampal and cortical low frequency oscillations. Exploration of familiar environment decreases the degree of this synchrony. Our data propose that novel visual information can induce high-power fluctuations in intrinsic excitability for both VC and hippocampus, potent enough to induce experience-dependent modulation of cortico-hippocampal connections. This interaction may comprise one of the endogenous triggers for long-term synaptic plasticity in the hippocampus.